Efektivitas Edukasi Gizi dan Kesehatan oleh Bidan dalam Mencegah Stunting pada Ibu Hamil dan Balita - Novitasari, Rista; Nufus, Hidayatun; Rosita, Evi (Jurnal Medicare, 2025)
Stunting remains a significant public health issue in Indonesia, with long-term impacts on child development. Midwives, as frontline health workers, play a critical role in delivering nutrition and health education to mothers during the crucial 1000 days of life to prevent stunting. Objective: This study aims to evaluate the effectiveness of nutrition and health education provided by midwives in increasing the knowledge of pregnant women and mothers of toddlers to prevent stunting. Methods: A quasi-experimental design with a one-group pretest-posttest approach was used involving 30 respondents (15 in the PowerPoint group and 15 in the leaflet group). Data were collected through structured questionnaires and analyzed using paired t-tests. Results: The PowerPoint group showed an average knowledge score increase from 36.7% to 84.9% (+48.2%), while the leaflet group increased from 32.3% to 70.1% (+37.8%). Statistical analysis showed a significant difference in knowledge improvement (p < 0.05), indicating that PowerPoint-based education was more effective than leaflets. Additionally, positive behavioral changes were observed in iron tablet adherence, posyandu attendance, and handwashing practices. Conclusion: Nutrition education delivered by midwives significantly improves maternal knowledge, especially when using audiovisual tools. Integrating such education into antenatal care and community health programs is recommended to enhance stunting prevention efforts.